Exploring differences in financial literacy across countries: the role of individual characteristics and institutions - Andrej Cupak; Pirmin Fessler; Maria Antoinette Silgoner; Elisabeth Ulbrich (Oesterreichische Nationalbank (OeNB), 2018)
We examine recently compiled microdata from the OECD/INFE survey covering information on the financial literacy of adult individuals from twelve countries around the globe. We find large differences in financial literacy across countries and decompose them into those explainable by differences in individual characteristics and those that cannot be explained by such differences. We show that individual characteristics matter with regard to differences in average financial literacy, but do not fully explain the observed differences. We further relate the unexplained differences in our microeconometric analysis to institutional differences across countries. We find strong relationships between the differences in financial literacy not explained by individual characteristics and life expectancy, social contribution rate, PISA math scores, internet usage, and to a lesser degree by GDP per capita, the gross enrolment ratio and stock market capitalization. Our results suggest that there is room for harmonization of economic environments across countries regarding decreasing inequality in the population's financial literacy.
Keywords: D14; D91; I20; 330; financial literacy gaps; inequality; decomposition analysis; counterfactual methods; personal finance; survey data